PEMANFAATAN LINGKUNGAN ALAM SEKITAR SEBAGAI SUMBER BELAJAR PADA MUATAN PELAJARAN IPA UNTUK SISWA MADRASAH IBTIDAIYYAH - Mawaddah, Nuril Aini (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research is motivated by the attention of researchers when teachers carry out science learning by utilizing nature and the surrounding environment as natural science learning resources. This research aims to: 1). Describe the use of the surrounding natural environment as a source of learning in science content for class V at MI Darul Hikmah. 2). Describe the weakness of using the surrounding natural environment as a source of learning content for class V MI Darul Hikmah Science class. This study used a qualitative descriptive approach. The research data were collected through observation, interviews, and documentation techniques. The data sources in this study were school principals, fifth grade science teachers, and fifth grade students at MI Darul Hikmah Darek. The data analysis technique used by researchers namely data condensation, data display, and conclusion drawing. Then the validity is checked by increasing persistence/persistence, triangulation and adequacy of references. This research shows that the use of the surrounding natural environment as a source of learning in science content for class V has been carried out properly and in accordance with the steps in learning, namely planning, implementing, and evaluating. The purpose of learning is to utilize the environment as a learning resource to equip students with meaningful experiences and strong memories that affect students' critical thinking skills and learning outcomes. The process of using the environment as a learning resource aims to overcome the shortage of science learning resources which are covered through the use of open nature such as rice fields and objects that exist in nature such as rocks, wood and soil. Regardless of that. In addition, the utilization of the surrounding natural environment as a source of natural science content learning aims to equip students with meaningful experiences and strong memories of a science concept. In addition, the use of the natural environment as a natural science learning resource is applied as an alternative solution in overcoming the limitations of supporting facilities and infrastructure learning activities.